Peran Kepala Sekolah sebagai Supervisor dalam Melaksanakan Supervisi Akademik yang Efektif - Siti Khanifah Asfiati; Rejokirono Rejokirono; Rahmat Mulyono; Saryanto Saryanto (Universitas Islam Negeri Sumatera Utara Medan, 2026)
This study aims to describe the role of the school principal as a supervisor in implementing effective academic supervision at Perak Junior High School Yogyakarta. Previous studies have rarely examined this role empirically in the context of Indonesian junior high schools with a structured, reflective supervision system. A descriptive qualitative approach was employed, involving one school principal and five teachers selected through purposive sampling. Data were collected via in-depth interviews, classroom observations, and documentation, then analyzed through data reduction, display, and conclusion drawing. Trustworthiness was ensured through source and technique triangulation, member checking, and audit trail. The findings reveal that effective academic supervision encompasses systematic planning, objective classroom observation, constructive feedback, and concrete follow-up. The principal functions as planner, observer, evaluator, professional coach, facilitator, and communicator, fostering a reflective learning culture. Academic supervision conducted twice per academic year positively improved teachers’ instructional skills and use of learning media. These results indicate that supervision effectiveness depends on humanist, collaborative, and evidence-based principal leadership oriented toward sustained learning quality improvement.